In conversation with Barney: a critical discourse analysis of interaction between a child with autism and his co-participants - Geils, Catherine (Rhodes University, Faculty of Humanities, Department of Psychology, 2004)
My study arose in the context of an intervention programme aimed at the development of a child with autism's communication and social interaction skills. The approach I take is a social constructionist one in which language is considered to be constructive and constitutive of social and psychological reality. This orientation challenges the assumptions of a western psychiatric approach that emphasizes the impairment and deficits associated with autism. The participants of the study are a 6-year-old boy diagnosed with Pervasive Developmental Disorder (Autistic Spectrum), and his mother, father, sister and a volunteer on the intervention programme. The discourse analytic method of conversation analysis is employed as a means of elucidating the collaborative mechanisms employed by both the child and his co-participants in making sense of one another. The specific aims of the study are to closely examine the communicative behaviour and interactive styles of the child and his coparticipants, their implications for communicative success (co-ordinated interaction) or breakdown (discordant interaction), and the implications for how the child is positioned within the discourse in relation to his co-participants. My constructions of the data suggested that a playful, activity-based interactive style constituted by non-verbal turns, affection and short, simple utterances enhance mutual participation and the accomplishment of co-ordinated interaction. Barney's co-participants sometimes tend to dominate interaction and frequently employ a strategy of repetitive questioning, which functions to direct and constrain the interaction and results in the child's withdrawal and discordant interaction. This tendency to withdraw, however, seems to function as a means by which the child is able to actively resist positioning by others, and thus constitutes himself in a position of greater power. Furthermore, his use of the pronoun 'I' and collaborative negotiation of the words yours and mine suggest the active co-construction and positioning of himself as a separate person in relation to his co-participants. This research informs intervention efforts and encourages the co-participants to reflect on how interaction is co-constructed between themselves and the child.
Keywords: Autism in children -- Case studies; Autistic children; Autistic children -- Rehabilitation; Discourse analysis; Children and adults; Language acquisition; Conversation; Children -- Language